Observational Study on the Socio-demography of Diabetic Depressive Patients in Tertiary Level Hospitals (Green Life Medical College Journal, 2026)
Introduction: Diabetes Mellitus is one of the most common disease. Associated depression is more common among Diabetic patients. This study was done aimed to assess the sociodemographic condition of the diabetic depressive patient and bring of social awareness.Methods: This observational prospective study was conducted among patients of diabetic depressive patient consulting at the Department of Psychiatry and Endocrinology Department of Sir Salimullah Medical College & Hospital & BIRDEM during the period of January 2018- December 2018.Results: According to the study, people who were commonly affected by diabetes and depression were selected. The patient’s age range were between 40 to 68 years. Among the patient’s 5 (14.3%) were males and 30 (85.7%) were females. Here, most of the patient’s monthly income ranges between- 20000-30000 taka and it was 42.86%. Among the 35 patients, 9 (25.7%) had minor depression and 26 (74.3%) are moderate to severe depression.Conclusion: A significant proportion of females were suffering from type-2 diabetes with depression. For our better social and family life, we should take care of our women. Journal of Green Life Med. Col. 2026; 11(1): 19- 22